2020
DOI: 10.1093/ehjcvp/pvaa128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statin therapy on SARS-CoV-2 infection-related mortality in hospitalized patients

Abstract: Aim Assessing the effect of statin therapy at hospital admission for COVID-19 on in-hospital mortality. Methods and Results Retrospective observational study. Patients taking statins were 11 years older and had significantly more comorbidities than patients who were not taking statins. A genetic matching (GM) procedure was performed prior to analysis of the mortality risk. A Cox proportional hazards model was used for the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 32 publications
8
80
1
5
Order By: Relevance
“…The putative benefit of statins in the context of COVID-19 is inconsistent across multiple studies and requires verification in prospective RCTs. Conversely, the preponderance of evidence suggests that statins are not likely harmful and do not need to be discontinued in the hospital ( Masana et al., 2020 ). Many of the reports do not describe the presence or absence of atherosclerotic vascular disease in statin users with COVID-19.…”
Section: Intracellular and Extracellular Cholesterol Lipids And Stamentioning
confidence: 99%
“…The putative benefit of statins in the context of COVID-19 is inconsistent across multiple studies and requires verification in prospective RCTs. Conversely, the preponderance of evidence suggests that statins are not likely harmful and do not need to be discontinued in the hospital ( Masana et al., 2020 ). Many of the reports do not describe the presence or absence of atherosclerotic vascular disease in statin users with COVID-19.…”
Section: Intracellular and Extracellular Cholesterol Lipids And Stamentioning
confidence: 99%
“…Initially, 24 eligible observational studies were identified that reported valuable data on in-hospital mortality and/or COVID-19 disease severity, including three studies of patients with diabetes [14] , [15] , [17] . Of these selected studies, 14 provided data on in-hospital mortality [15] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ( Table 1 )—although one reported only adjusted hazard ratios (HRs) with no crude numbers of deaths in statin users vs non-users and, therefore, could not be included in the meta-analysis (authors were contacted, but did not communicate their results) [26] —while 11 studies reported data on COVID-19 severity (as determined by ICU, IMV; Table 2 ) [18] , [22] , [23] , [27] , [28] , [30] , [31] , [32] , [33] , [34] , [35] . Also, a study by Tan et al [36] collected very few events in a Chinese population (personal communication from the authors), thereby preventing the use of this study in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The included observational studies reporting data on in-hospital mortality are listed in Table 1 [15] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . Results of the corresponding meta-analysis are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations